Dynamic identification and monitoring of historical masonry structures: case study of St. Torcato Church - Ramos, Luís F. (2009)
Considering the modern conservation criteria that demands minimum intervention and preservation of construction techniques, understanding of any damage phenomena or evaluation of seismic vulnerability have significant importance. For this purpose identification of a structure or mathematic model must represent the existing properties and conditions. In that point different non-destructive inspection techniques are being used that provide local information for estimation of global properties. However, seismic behaviour of a structure or any possible earthquake damage occurrence is depending on global dynamic properties. Dynamic behaviour of structures is defined by the mechanical properties of the materials, geometry of the structure and its energy dissipation capabilities. When those variables are known, seismic response of a structure can be analyzed for different earthquake excitations. These variables are controllable in design processes with many safety coefficients. For the analysis of existing historical structures, to evaluate their safety, those variables are difficult to estimate even with the help of destructive or non-destructive structural tests. Experimental dynamic identification techniques, which are based on the acceleration records of a structure, allow us to obtain natural frequencies, mode shapes and damping coefficients of a structure. These data represent the overall dynamic capacity of a structure as a result of its physical properties that are unknown or difficult to obtain. By this way, real response of the structure under specified or unknown excitations can be used to modify structural models with any test results that represent only local properties. In addition to dynamic identification, dynamic measurements may perform for monitoring. Dynamic monitoring provides information about changes in structural response under environmental cycles or any external excitations such as traffic or earthquakes. Changes of dynamic response by time can be related with the loose of support conditions or decrease of material properties by means of deterioration or local damages. In this sense, dynamic monitoring can be used as a warning system indicating overall deficiencies on the structure or to check the efficiency of any previous interventions.